2022
DOI: 10.1002/cctc.202200889
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Catalysis Under Magnetic Fields: Methodologies, Advances, and Trends

Abstract: Magnetic field‐enhanced catalysis is an advanced strategy for enhancing catalytic reactions that have emerged in recent years, presenting great potential for alleviating the energy crisis and environmental pollution. Under favorable non‐contact magnetic field conditions, the external magnetic field that produces the enhancement effect can provide additional energy to the catalytic system as an additional driving force for the catalytic reaction and thus positively improve the overall catalytic efficiency. Expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…‐ Following an early observation performed in 2005, [165] the application of magnetic fields during the operation of bioelectrochemical devices can improve their performance. Indeed, a wider use of magnetic fields has since been established as stimuli for magnetothermal effect, magnetohydrodynamics and spin polarisation [2,194] and demonstrated a positive effect on enzymatic activity [195] . In this respect, the improved reactivity of biomolecules [196] in response to external magnetic fields has recently been studied, leading to the radical pair mechanism [197] as a possible explanation for the improved performance of biomolecules that support radical recombination reactions [198] .…”
Section: Discussionmentioning
confidence: 99%
“…‐ Following an early observation performed in 2005, [165] the application of magnetic fields during the operation of bioelectrochemical devices can improve their performance. Indeed, a wider use of magnetic fields has since been established as stimuli for magnetothermal effect, magnetohydrodynamics and spin polarisation [2,194] and demonstrated a positive effect on enzymatic activity [195] . In this respect, the improved reactivity of biomolecules [196] in response to external magnetic fields has recently been studied, leading to the radical pair mechanism [197] as a possible explanation for the improved performance of biomolecules that support radical recombination reactions [198] .…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in BE suggested that the outer electrons in the nanocomposite with lower energy can be more readily excited under the influence of AMF, thereby facilitating the electron transfer in the conversion of H 2 O 2 into •OH. [31] Moreover, additional enzymatic-like properties including OXD and superoxide dismutase (SOD) was investigated. Drawing inspiration from the ROS generation mechanism in photonic catalysis, a pronounced OXD function was observed in PZF under visible light irradiation produced by Xenon lamp for 10 min.…”
Section: Multienzyme-like Behavior Exposed To Light and Alternated Ma...mentioning
confidence: 99%
“…In recent work, Bhattacharjee et al used constrained density functional theory formalism to investigate the role of spin orientation on the reactivity of ORR intermediates on a ferromagnetic electrode surface. 34 They considered the direct dissociative process (12) where "*" represents the adsorption site, and they showed that the strength of binding for these reaction intermediates (O*, HO*) depends on their relative spin orientations with respect to the magnetization of the electrode. The authors suggest that oxygen-based electrochemical reactions can be controlled through an applied magnetic field and demonstrate this possibility by studying an ORR on a PdFe(001) surface using a new concept called spin orientation dependent overpotential.…”
Section: Down Spinmentioning
confidence: 99%
“…Magnetic fields can influence the energy levels of active species by interacting with their spin states, which can affect catalytic properties and alter the selectivity of the reaction. 12 In the case of alloy catalysts, the effect of magnetism becomes even more prominent due to the charge transfer between the components. The interplay between charge transfer and magnetism can affect the activity and selectivity of alloy catalysts, and this has been investigated in several studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation